2019
DOI: 10.3390/rs11060655
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Machine Accuracy Assessment for Extracting Green Urban Areas in Towns

Abstract: The most commonly used model for analyzing satellite imagery is the Support Vector Machine (SVM). Since there are a large number of possible variables for use in SVM, this paper will provide a combination of parameters that fit best for extracting green urban areas from Copernicus mission satellite images. This paper aims to provide a combination of parameters to extract green urban areas with the highest degree of accuracy, in order to speed up urban planning and ultimately improve town environments. Two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Table 3 shows the coordinates of the center of the study area in Varaždin and Osijek. Figure 1 shows the study areas with a signature and control samples [15].…”
Section: Study Areas and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 shows the coordinates of the center of the study area in Varaždin and Osijek. Figure 1 shows the study areas with a signature and control samples [15].…”
Section: Study Areas and Resultsmentioning
confidence: 99%
“…The authors in [14] compared the random forest, K nearest neighbor, and SVM algorithms for land cover classification using Sentinel-2 imagery and concluded that SVM provided the best results. The authors in [15] explored how different kernels affect the land cover classification results using Sentinel-2 imagery. They found that the radial basis function produced the highest accuracy and proposed further research using different machine learning methods.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations